Enhancing Building Condition Assessment (BCA) Practices At UTHM: Identifying Challenges and Proposing Strategic Solutions - Nurul Nasuha Nazeri; Mohammad Asyraf Abdul Rahman (Progress in Engineering Application and Technology, 2026)
Building Condition Assessment (BCA) is an important procedure for maintaining the sustainability, functionality and safety of institutional buildings especially in university environments where usage is continuous. However, the lack of organised supporting systems, limited funds and manual evaluation processes often have an impact on how effectively BCA is implemented. The purpose of this study is to identify Universiti Tun Hussein Onn Malaysia's (UTHM) current BCA practices and implementation issues and to provide improvement solutions based on feedback from engineering practitioners. A mixed-method sequential approach was used with engineering practitioners completing a questionnaire survey after structured interviews with a selected group of UTHM staff. The information collected was evaluated using descriptive statistical analysis. The results show that BCA at UTHM is mostly carried out by manual inspections with the main barriers including a shortage of manpower, insufficient technical expertise, a lack of standar operating procedures and inconsistent management of data. The study comes to the conclusion that in order to improve the efficacy of BCA practices in institutional buildings, standardisation guidelines, enhanced staff training and an evolving implementation of digital tools are essential.